Collagen remodelling and plasma ascorbic acid levels in patients suspected of inherited bleeding disorders harbouring germline variants in collagen‐related genes. Issue 1 (7th November 2020) - Fager Ferrari, Marcus; Zetterberg, Eva; Rossing, Maria; Manon‐Jensen, Tina; Pehrsson, Martin; Karsdal, Morten A.; Lykkesfeldt, Jens; Leinoe, Eva
Abstract: Introduction: Variants in collagen‐related genes COL1A1, COL3A1, COL5A1 and COL5A2 are associated with Ehlers‐Danlos syndrome (EDS), a heterogeneous group of connective tissue disorders strongly associated with increased bleeding. Of patients with incompletely explained bleeding diathesis, a relatively high proportion were shown to harbour at least one heterozygous variant of unknown significance (VUS) in one of these genes, the vast majority without meeting the clinical criteria for EDS. Aim: To investigate the functional consequences of the identified variants by assessing the formation and degradation of types I, III and V collagen, in addition to plasma levels of ascorbic acid (AA). Methods: A total of 31 patients harbouring at least one heterozygous VUS in COL1A1, COL3A1, COL5A1 or COL5A2 and 20 healthy controls were assessed using monoclonal antibodies targeting neo‐epitopes specific for collagen formation and degradation. Plasma AA levels were measured in patients using high‐performance liquid chromatography. Results: Serum levels of C5 M (degradation of type V collagen) were decreased in patients compared with healthy controls ( p  = .033). No significant differences were found in biomarkers for remodelling of types I and III collagen. A significant negative correlation between bleeding (ISTH‐BAT score) and plasma AA levels was shown ( r  = −.42; r 2  = .17; p  = .020). Suboptimal or marginally deficient AA status was found in 8/31 patients (26%). Conclusion: Functional investigations of collagen remodelling were not able to identify any clear associations between the identified variants and increased bleeding. The negative correlation between plasma AA levels and ISTH‐BAT score motivates further investigations.